1985
DOI: 10.1002/qua.560280611
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations of the electronic states of porphyrins. III. Low‐lying electronic states of porphinatoiron(II)

Abstract: Ab initio configuration interaction calculations are reported on the lowest quintet, triplet, and singlet states of Fe"(P). Due to the large number of states found, a catalog of the low-lying states is presented. Novel triplet and quintet charge-transfer states are reported as low as 1.3 eV. These states are d S (S = 5/2) on the iron low-spin-coupled to the radical anion excited porphyrin ring (S = 1/2 or 3/2). Oscillator strengths originating from each of three low-energy triplet states are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
(19 reference statements)
2
23
1
Order By: Relevance
“…Previous ab initio calculations on FeP based on Hartree-Fock (HF),26 configuration interaction (CI),27 MRMP,28 and CASPT228,29 methods, all predicted a high-spin (S = 2) quintet as the ground state for this complex, in disagreement with experiment. This failure was ascribed to the fact that the stability of the high-spin state is always exaggerated in the HF-type theories since they contain only Fermi correlation, but not Coulomb correlation 30.…”
Section: Introductionmentioning
confidence: 76%
“…Previous ab initio calculations on FeP based on Hartree-Fock (HF),26 configuration interaction (CI),27 MRMP,28 and CASPT228,29 methods, all predicted a high-spin (S = 2) quintet as the ground state for this complex, in disagreement with experiment. This failure was ascribed to the fact that the stability of the high-spin state is always exaggerated in the HF-type theories since they contain only Fermi correlation, but not Coulomb correlation 30.…”
Section: Introductionmentioning
confidence: 76%
“…On the other hand, Raman spectra of FeOEP were interpreted in terms of an 3 E g state arising from the (d xy ) 2 (d ) 3 (d z 2) 1 configuration. 8 From the theoretical perspective, Hartree-Fock ͑HF͒ calculations on the unsubstituted iron porphine ͑FeP͒ agree with experiment that 3 A 2g is indeed the most stable of various triplet states, [9][10][11][12] but find a high-spin 5 A 1g state to be even lower in energy by more than 1 eV. 9,10,12 The inclusion of correlation helps to repair this artificial advantage of the quintet, 12 but does not fully reverse the incorrect order of spin multiplicities.…”
Section: Introductionmentioning
confidence: 83%
“…8 From the theoretical perspective, Hartree-Fock ͑HF͒ calculations on the unsubstituted iron porphine ͑FeP͒ agree with experiment that 3 A 2g is indeed the most stable of various triplet states, [9][10][11][12] but find a high-spin 5 A 1g state to be even lower in energy by more than 1 eV. 9,10,12 The inclusion of correlation helps to repair this artificial advantage of the quintet, 12 but does not fully reverse the incorrect order of spin multiplicities. In the same vein, recent CASPT2 and MRMP studies 13 of FeP remain in disagreement with experiment [3][4][5][6][7][8] in predicting the lowest state to be 5 A 1g .…”
Section: Introductionmentioning
confidence: 83%
“…In all cases the charge is mainly localized on the iron atom. This fact has also been stressed by, for example, Ohno [9] and Rawlings et al [14], who found that the charge on Fe was + l . l for all three low-lying triplets.…”
Section: Iron Porphinementioning
confidence: 67%
“…This indicates that for the long distance case the iron is in the Fe(I1) state, whereas in the short distance case it is in the Fe(II1) state. It should be noticed that the ab initio calculations of Rawlings et al [14] gave a d-electron population on Fe(I1) of 6.2 and on Fe(II1) of 5.4 in FeP. These numbers are in good agreement with the ab initio calculations on other iron complexes, where it was found that the d-orbital population was 6.2 in the Fe(I1) complexes of glyoxal and dithiolenes and 5.5 in the corresponding Fe(II1) complexes [40-421. The above indicates that the molecule can undergo an oxidation-reduction reaction when the pyridine molecules are moved from longer to shorter distances.…”
Section: Bis(pyridine)(porphinato)ironmentioning
confidence: 98%